ENVIRONMENTAL GEOLOGICAL EVALUATION FOR THE DEVELOPMENT OF SENTOLO SUBDISTRICT AND SURROUNDING AREA, KULON PROGO REGENCY, YOGYAKARTA SPECIAL REGION. - Ilham Mughni, Fajri
The Kulon Progo Regency area is in the administrative area of the Special Region of Yogyakarta (DIY) Province, this area has several places that are developed from an economic and environmental perspective, such as the construction of the Yogyakarta International Airport (YIA) in the west of the research area, iron sand mining in Progo River and development of the Sentolo Industrial Area. The development plan for the Kulon Progo Regency area requires an analysis of territorial discretion based on the concept of environmental geology and an evaluation of land use from the 2012-2032 RTRW of Kulon Progo Regency. The research area is located at coordinates 9117261 – 9132597 mU and 405279 – 420167 mT (UTM WGS 1984 Zone 49S) which are administratively located in Sentolo, Wates, Lendah, Galur, Pengasih, and Panjatan Districts, Kulon Progo Regency, Special Region of Yogyakarta Province (DIY) with an area of 168.7 Km2. The methods used include literature studies, field mapping, and environmental geology analysis using the Analytical Hierarchy Process (AHP) method. The assessment criteria used in the environmental geological analysis are divided into groundwater criteria (groundwater depth, groundwater quality, aquifer productivity, groundwater conservation zone), accessibility (distance to roads, distance to settlements, distance to rivers, land use, slopes+ altitude), surface physical aspects (rock hardness and soil density, and also slope) and disaster hazards (volcano hazard, earthquake hazard, landslide vulnerability, tsunami hazard, and liquefaction vulnerability), as well as boundary components (coastal boundaries, river borders, high earthquake hazard zone, high tsunami hazard and high liquefaction vulnerability). The data used comes from thematic maps, rock samples, and hydrogeological data which are compiled and digitized to produce an overlaid map of environmental geological parameters. Environmental geological analysis shows land area zoning with the percentage of Very Discretion Zone (14.7%), Fairly Discretion Zone (71.8%), Less Discretion Zone (1.2%), and Not Discretion Zone (12.3%). The results of the evaluation of the suitability of land use for Cultivation Areas in the RTRW of Kab. Kulon Progo 2012-2032 shows residential areas are still in the Not Discretion -Very Discretion Zone, agricultural areas are in the Not Discretion -Very Discretion Zone, industrial areas are in the Less Discretion -Fair Zone, and mining areas are in the Not Discretion -Less Zone Discretion.